TEKNIK PENYADAPAN PINUS UNTUK PENINGKATAN PRODUKSI MELALUI STIMULAN HAYATI - Sukadaryati; Dulsalam (BRIN Publishing, 2013)
The increased demand of pine resin both for domestic and overseas markets has necessitated efforts to enhance pine-sapproduction. The use of strong acid-based conventional stimulants has been long employed by Perum Perhutani, butquestions arise regarding the environment effect as well as growth survival of the tapped pine trees. Consequently, the use ofbiostimulant deserves thorough consideration, since not only will assure friendly-environmental effects but also securing thesustainability of the pine trees. An experiment was conducted to look into the effect of using biostimulants on theproduction of sap (exudates) from the tapped pine trees. Three tapping techniques were employed, i.e. mujitech, boring andkedukul. The biostimulant consisted of three kinds (lengkuas, kencur, and red onion), each with three concentration levels(50%, 75%, and 100%).It turned out different tapping techniques seemed not affecting the pine-sap production, nor did the effect of biostimulantconcentrations (50-100%). However, different kinds of biostimulants did so, whereby lengkuas afforded the sap-yieldincrease the highest (268%) compared to the control (without biostimulants), followed in order by kencur (206%) and redonion (180%). Use of the second and third caused no significant difference. Economically, the use ofbiostimulant at 50% concetration was effective enough. Further attempts are neseccary to find other alternativebiostimulants.